MANAJEMEN PEMERINTAHAN DAERAH KOTA PEKANBARU TERHADAP PELAKSANAAN PROGRAM AREA TRAFFIC CONTROL SYSTEM (ATCS) TAHUN 2019 - Imalia Novria; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Area Traffic Control System (ATCS) is traffic control by aligning red light times on the highway network of a city. Traffic regulation through this system requires parameters of the number of vehicles and vehicle travel time. The traffic rhythm arrangement will be better if it applies the Area Traffic Control System (ATCS) technology at all traffic intersections in the city. The purpose of this study is to describe the Regional Government Management of Pekanbaru City on the Implementation of the Area Traffic Control System Program in the yearThe research approach used is a qualitative approach. This type of research is descriptive. The research location is at the Transportation Department of Pekanbaru City. Types and sources of research data were divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to ATCS. Data collection techniques used by interview and documentation. Meanwhile, data analysis was performed using qualitative analysis.The results of this study are that the Regional Government Management of Pekanbaru City on the Implementation of the Area Traffic Control System Program in 2019 has not been carried out optimally, there are still problems found in the field due to several factors, namely limited budget funds, lack of quality and quantity of resources owned, lack of public understanding. to the ATCS program and the lack of awareness in traffic. Keywords: Local Government Management, Program Implementation, ATCS